Volume 1: Turbomachinery 1992
DOI: 10.1115/92-gt-036
|View full text |Cite
|
Sign up to set email alerts
|

Recess Vane Passive Stall Control

Abstract: An experimental investigation has been carried out on the influence of a vaned recessed casing treatment on the stall margin improvement of axial flow fans with different hub to tip ratio, with and without inlet distortion. The inlet distortion tests were conducted on a 0.5 hub to tip ratio fan and significant increases in the flow range with only small drops in operating efficiency were observed. The clean flow tests were conducted on higher hub to tip ratio fans (0.7 and 0.9). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This results in a tendency towards an early stalling regime. Ziabasharhagh et al [9] also showed that scaling of the casing treatment in proportion to the blade chord was a reliable design criteria. Further analysis of these results indicated that a depth of 50 mm would be sufficient to expect a reasonable stall margin improvement.…”
Section: Physical Description Of the Casing Treatmentmentioning
confidence: 96%
See 2 more Smart Citations
“…This results in a tendency towards an early stalling regime. Ziabasharhagh et al [9] also showed that scaling of the casing treatment in proportion to the blade chord was a reliable design criteria. Further analysis of these results indicated that a depth of 50 mm would be sufficient to expect a reasonable stall margin improvement.…”
Section: Physical Description Of the Casing Treatmentmentioning
confidence: 96%
“…It also appears that axial chord exposure is independent of loading. Miyake and Inaba [7], for instance, used an industrial fan with 15 blades and low loading, whereas Azimian et al [8], Ziabasharhagh et al [9] and Kang et al [4] all conducted experiments on a fan with 27 blades and aero-engine loading. With this knowledge, a casing treatment was built for the experimental fan with the facility to vary the amount of rotor axial chord exposure.…”
Section: Physical Description Of the Casing Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were very encouraging with superior stall margin and less efficiency sacrifice when compared to conventional slot type treatments. In addition , Ziabasharhagh et al(1992) casing treatments were capable of increasing stall margin for a range of machines and also able to increase tolerance to inlet flow distortion.…”
Section: Introduction Introductionmentioning
confidence: 99%
“…Takata et al(1977), Smith et al (1984( ), Johnson et al(1987 and Crook et al(1993), but few on vaned recess casing treatments. Ziabasharhagh et al(1992), however, based on the 'wool tuft flow study provided a hypothesis of the operation from which the following physical description of the flow may be deduced as sketched in Fig.l. The low momentum fluid, associated with stalling flow is centrifuged towards the blade tip and then recirculates axially as shown in Fig.1-a and also circumferentially in the untreated fan.…”
Section: Introduction Introductionmentioning
confidence: 99%